THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. PACIFIC MEDAN INDUSTRI (PAMIN) - Evayanti Panjaitan (Universitas Efarina, 2025)
This study aims to analyze the influence of motivation and work discipline on employee performance. The evaluation disposition put into practice a decimal drawing near with fragmentary T-test psychoanalysis and contemporaneous F-test. The consequences of the contemplate demonstrate that a certain extent motive (X1) has a cocksureness on the other hand undistinguished chain reaction on worker accomplishment (Y) with a T-statistic expenditure of 1. 583 and a p-value of 0. 113 (> 0. in the meantime elbow grease drilling (X2) has a cocksureness and substantial chain reaction on worker accomplishment with a T-statistic expenditure of 2. 103 and a p-value of 0. 036 (< 0. Simultaneously, motive and elbow grease drilling chalk up a substantial chain reaction on worker bringing off with an F-statistic expenditure of 12. 933 and a p-value of 0. 000 (< 0. These discoveries demonstrate that although motive does not chalk up a substantial chain reaction a certain extent its continuance all the more furnishes when composed with elbow grease drilling in rising worker performance. This contemplate counsels that fellowships accommodation bounteous importance on rising elbow grease drilling nailed down crystallise regulations and supervision, as advantageously as invigorating worker motive nailed down awards, continuance adding to and a contributive elbow grease surrounding.